Krisis Global dan Ketahanan Sumber Pembiayaan Pembangunan: Kajian Literatur atas Peran Tabungan Domestik sebagai Stabilizer - Yourman Gamas Mahesa; Elly Lestari; M Daffa Dhiya Ulhaq; Ival Fadlyanto; Dede Saerozi; Muhtar Ulum; Mochammad Yuda Adipratama; Nissya Rahma Aurelia Rokhim; Gama Pratama (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
Development financing systems in various developing countries, including Indonesia, have been tested by repeated global crises, such as the 2008 financial crisis, the COVID-19 pandemic, and geopolitical tensions since 2020. The economy is highly dependent on external funding, such as foreign loans and foreign direct investment (FDI), making it vulnerable to disruptions and uncertainty in capital flows. This article examines the strategic role of domestic savings as a stabilizer in maintaining the resilience of development financing using a desk study approach. The literature review shows that mobilizing domestic savings through conventional and Islamic financial institutions is crucial for encouraging long-term investment, reducing dependence on external financing, and strengthening national fiscal independence. In the Islamic economy, the rise of yield-based savings instruments, productive waqf, and retail sukuk has helped expand a stable and equitable domestic funding base. Furthermore, this article finds that digital transformation, fiscal incentive policies, and financial literacy are key to increasing public participation in productive savings. Therefore, increasing domestic savings is an economic tool and a national defense strategy in facing ongoing global crises.